Сучасний освітній процес: курс на дистанційне навчання - Ключко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна; Сирцов, Вадим Кирилович; Kluchko, S. S.; Evtushenko, V. M.; Syrtsov, V. K. (My University, 2017)
В умовах реалізації основних освітніх програм важливе місце набуває система дистанційної освіти. У статті за допомогою системного аналізу досліджено основні принципи створення дистанційних курсів, які впроваджуються в освітній процес на кафедрі гістології, цитології та ембріології ЗДМУ. Запропоновані методи розробки дистанційного курсу мають за мету створити комфортні умови навчання, за яких студент буде відчувати свою успішність, інтелектуальну спроможність, що робить більш продуктивним сам процес навчання. Background. In the conditions of implementation of basic educational programs, an important place is acquired by the system of distance education. In the article with the help of system analysis the main principles of creating distance courses that are introduced into the educational process at the Department of Histology, Cytology and Embryology of ZSMU are investigated. Results. Proposed methods of developing a distance course are designed to create comfortable learning conditions in which the student will feel successful, intellectually sound, which makes the learning process more productive. The activities of the student must planned during the distance learning process using information materials of different authors. If in the first case attention is paid to the quality of the text, the qualitative educational process does not always guarantee, in the second case the quality of the educational process is important, which requires organizational and methodical activities, as well as high quality information materials that can be developed by different authors. Conclusion. To maintain a high level of clinical thinking and create conditions for independent learning activities, distance learning provides internal motivation for students to learn.
Modern educational process: distance learning course
Keywords: дистанційний курс; студенти; віртуальне навчальне середовище; distance course; students; virtual learning environment